Bulwer's Petrel in Indonesia - Marc Argeloo; Rene Dekker (Indonesian Ornithologists’ Union, 1996)
Based on observations of 15 and 14 Bulwer's Petrels in Sulawesi and Irian Jaya respectively, the occurrence of the species in Indonesia is described.